DIVERSE EFFECT OF CADMIUM AND LEAD ON GROWTH AND YIELD OF CARROT (DAUCUS CAROTA) - ZAHID AHMAD MALIK,; EUGENIA P. LAL,; ZAHOOR AHMAD MIR, (International Journal of Pharma and Bio Sciences, 2014)
The aim of the present study was to investigate the uptake of cadmium and lead by carrot from the soil contaminated with lead and cadmium. Cadmium and lead were artificially added to the soil tank and seeded with carrot seed. After growth and cultivation the samples were randomly selected from the different tanks and subjected to root and leaf analysis through atomic absorption spectrometry (AAS) for Cd and Pb. Along with plant parts, soil was also analyzed for the same. The result showed that the levels ranged from 0.011 to 0.0315 for lead in soil followed by root 0.006 to 0.183 and leaves 0.002 to 0.036. Cadmium concentration ranged from 0.008 to 0.059 in soil and 0.004 to 0.022 was accumulated by root followed by leaf 0.001 to 0.016. Plant samples had concentration of Cd and Pb exceeded the FAO-WHO limits. The maximum concentration of lead and cadmium were found in T3>T2> T1 >T0. It was found that all the parameters like plant height, number of leaves, number of branches, fresh weight and dry weight (yield) of the carrot decreases with increases in both lead and cadmium concentrations in comparison to control To. In the present study it was found that carrot uptakes both the heavy metals (Cd and Pb) which has an inhibitory effect on a carrot.